Freedom of expression in unpredictable times: stakeholders' perceptions of Malaysia's track record in the 3rd UPR cycle - Wan Mohd Nor, Murni; Syed Hussien, Sh Fatimah Alzahrah; Sheikh Ghazali, Lubna; Mohammad Fuad, Farah Mursyieda; Ab Razak, Shahir; Mohamed Khairi, Mohd Firdaus (Institute of Diplomacy and Foreign Relations (IDFR), MINISTRY OF FOREIGN AFFAIRS, MALAYSIA, 2024)
Since Malaysia's involvement in the 3'd Universal Periodic Review (UPR) in 2018, there have been some improvements related to freedom of expression which reflects the government's commitment to enforce accepted UPR recommendations. However, the unpredictable political situation from 2018- 2021 resulted in two government changes and three different Prime Ministers. These changes have obstructed intended human rights reforms, which afforded more opportunities for state intervention in freedom of expression-particularly during the height of managing COVID-19. All these developments have made it even more challenging to evaluate human rights reforms by the government. This paper discusses Malaysia's human rights track record in general and freedom of expression in particular via in-depth interviews with 23 stakeholders in related fields. Findings indicate notable progress such as legal reforms, bolder media practices, heightened public awareness of freedom of expression, and increased activism of CSOs. However, the study also identified problems which manifested in restrictions on freedom of expression such as the questioning of journalists, crackdowns on migrants and refugees, as well as investigations against leaders of CSOs and activists. Implications of these findings on the implementation of accepted UPR recommendations are also discussed.